Dinamika stok ikan teri di pasar mingguan Kecamatan Kolono Timur Kabupaten Konawe Selatan : Dinamika Usaha Perikanan - Kusuma, Umar Adi; Yusuf, Sarini; Piliana, Wa Ode; Rosmawati; La Ola, La Onu; Sarifin, Abdul (Jurnal Sosial Ekonomi Perikanan, 2024)
This study aims to determine the dynamics of anchovy stocks in the weekly market in East Kolono District, South Konawe Regency, namely the Langkatulu market, Rumba-Rumba market, and Lambangi market in May 2022. The sample of this study was 14 people, namely from Langkatulu Market as many as 5 people consisting of 1 seller of fresh anchovies and 4 sellers of dried anchovies, 4 people of Rumba-Rumba Market consisting of 1 seller of fresh anchovies and 3 sellers of dried anchovies, and Pasar Lambangi as many as 5 people consisting of 4 people sellers of fresh anchovies and 1 seller of dried anchovies. The variables observed were the stock of dried anchovy and fresh anchovy. The data were analyzed using simple statistical calculations in the form of percentages. The result of the analysis show that the dynamics of the anchovy stock for four weeks at the weekly market in the Kolono Timur sub-district is always dynamic every week.